2021
DOI: 10.1007/s11695-021-05341-w
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Predict Weight Loss After Bariatric Surgery?—External Validation of Predictive Models

Abstract: Background Bariatric surgery is the most effective obesity treatment. Weight loss varies among patients, and not everyone achieves desired outcome. Identification of predictive factors for weight loss after bariatric surgery resulted in several prediction tools proposed. We aimed to validate the performance of available prediction models for weight reduction 1 year after surgical treatment. Materials and Methods The retrospective analysis included patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
16
3
Order By: Relevance
“…3B). Postoperative weight loss prediction models have been developed for bariatric surgeries and have been able to predict weight loss with an accuracy of R 2 ranging from 0.24 to 0.75 [20][21][22][23]. Even though the R 2 values in these studies were higher than ours, R 2 in these studies was still low.…”
Section: Annals Of Clinical Nutrition and Metabolismcontrasting
confidence: 58%
See 1 more Smart Citation
“…3B). Postoperative weight loss prediction models have been developed for bariatric surgeries and have been able to predict weight loss with an accuracy of R 2 ranging from 0.24 to 0.75 [20][21][22][23]. Even though the R 2 values in these studies were higher than ours, R 2 in these studies was still low.…”
Section: Annals Of Clinical Nutrition and Metabolismcontrasting
confidence: 58%
“…The area in which research on predictive models of weight loss has been most active is bariatric surgery [20][21][22][23]. Predicting postoperative weight loss is also an important subject in other fields of gastrointestinal surgery, but only a few relevant studies have been conducted [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential implication of ingestive behavioral analyses may be the optimization of the preoperative counseling process. Existing models of bariatric weight loss prediction tend to overestimate the outcome ( 56 ). However, a recent study published by Perez-Leighton et al showed the utility of preoperative classification of patients according to their sucrose-wanting rating in the selection of BS type ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, they can serve as an invaluable source of prediction, provided they undergo appropriate analysis with AI tools. Nevertheless, despite the accumulated experience and evidence with bariatric surgery and its effectiveness, to date there is no accurate tool for weight loss prediction, and most clinical models tend to overestimate the bariatric outcome of the most commonly performed procedures [54].…”
Section: Ai As a Tool For Predicting Effectiveness Of Bariatric Surgerymentioning
confidence: 99%